Investigating nanoparticle properties in plasmonic nanoarchitectures with DNA by surface plasmon resonance imaging. Issue 30 (16th March 2015) - Mariani, Stefano; Scarano, Simona; Ermini, Maria Laura; Bonini, Massimo; Minunni, Maria
Abstract : The optimal optical coupling conditions between SPWs and nanoparticle LSPs can be achieved by overlapping the source wavelength with the wavelength of excitation of LSPs. Abstract : Nanoparticles with different sizes, refractive indices and plasmonic profiles are synthesized, labelled with DNA and embedded in DNA-based plasmonic nanoarchitectures. The contribution of the different properties to reflectivity variation % is rationally investigated by DNA hybridization measurements using the surface plasmon resonance imaging (SPRi) technology.